Growth and relative living standards: Testing barriers to riches on post-war panel data - Patrick Minford; David Meenagh; Jiang Wang (Cardiff University, Cardiff Business School, 2007)
The effect of business tax and regulation on growth, together with potential effects of government spending on education and R&D, is embodied in a model of a small open economy with growth choices. The structural model is estimated on post-war panel data for 76 countries and the bootstrap is used to produce the modelís sampling variation for the analysis of panel regressions of growth. Statistical rejection can occur at either the structural or the growth regression stage. The models featuring government spending on education and R&D are rejected while that with business taxation is accepted.
Keywords: O41; O57; C52; 330; growth; living standards; business regulation; business taxation; public education; government R&D; structural model; bootstrap testing; Wirtschaftswachstum; Lebensstandard; Forschungs- und Technologiepolitik; Regulierung; Steuerpolitik; Ökonometrisches Modell; Welt